Avaliação da participação do metabolismo da adenosina nos efeitos tardios da exposição embrionária ao etanol em peixe-zebra (Danio rerio) - Lutte, Aline Haab (2018)
Ethanol is one of the most commonly used psychoactive substances with addictive properties in the world. One of the consequences to ethanol use is the Fetal Alcohol Syndrome (FAS), characterized by a set of changes in the development of children whose mothers ingested ethanol during gestation. Ethanol affects several neurotransmission systems, including the purinergic system. The embryonic development period is a phase of great susceptibility to exogenous and endogenous agents and the perturbations capable of altering the adenosinergic signaling during the embryonic phase may be related to morphological, biochemical and behavioral changes that go from birth to adult life. In recent years, a substantial number of evidence has emerged demonstrating that the synthesis and metabolism of purines and pyrimidines play important roles in controlling embryonic and fetal development and organogenesis. Dysfunctions in normal adenosine homeostasis during early brain development may have important consequences in the formation of neuronal circuits, thus contributing to neurodevelopmental changes. In the chapters that follow this thesis different mnemonic, biochemical and behavioral alterations in zebrafish exposed to ethanol were discussed in two distinct stages of development and the possible role of adenosine in such alterations. In the first chapter, the damage caused by ethanol in the gastrula / segmentation and pharyngula stages in the mnemonic parameters was analyzed, and suggests that the changes in the control of adenosine levels caused by ethanol could alter the neuromodulation of important components in memory formation, such as neurotransmitters. It was shown that adjustment of adenosine levels by the inhibition of ecto-5'-nucleotidase appears to be effective in restoring normal adenosine levels and memory acquisition in animals exposed to ethanol during pharyngula stage. A decrease in the body size of the animals in the proportional analysis of the telencephalon / encephalon and cerebellum / encephalon at both stages was detected when compared to controls. In the second chapter were evaluated the changes caused by ethanol exposition in the gastrula / segmentation and pharyngula stages in the ecto-5'-nucleotidase and adenosine deaminase enzymatic activity, gene expression of the enzyme ecto-5'-nucleotidase, morphological parameters and in the quantification of adenosine in zebrafish encephalon. Exposure to 1% ethanol did not promote severe morphological effects, but a decrease in body length was observed. The enzymatic activity of the ecto-5'-nucleotidase was increased in adult 9 animals exposed to ethanol in the gastrula / segmentation stage. The ecto-5'-nucleotidase gene expression and the enzymatic activity of adenosine deaminase did not change significantly at both stages of development. The adenosine quantification did not show differences in nucleoside concentration in total encephalon of adult animals exposed to ethanol at early development. In the third chapter, the behavioral parameters of locomotion, anxiety, aggressiveness and social interaction were evaluated in animals at 3 and 12 months after fertilization (mpf) that were exposed to1% ethanol during gastrula / segmentation and pharyngula stages. In addition, was evaluated the use of inhibitors of the enzymes ecto-5'-nucleotidase (3 and 12 mpf) and adenosine deaminase (3 mpf) on the behavioral changes investigated. There were no significant changes in locomotor parameters. An anxiolytic profile was detected at 3 mpf in the ethanol exposed animals at both stages of development, however, this profile did not remain at 12 mpf and the use of the inhibitors did not generate significant effects in this parameter. The aggressiveness had a significant increase in ethanol exposed animals at the pharyngula stage at 3 mpf and remained increased at 12 mpf, being recovered with the use of the ecto-5'-nucleotidase inhibitor. The social interaction decreased in the ethanol exposed animals in both stages of development at 3 mpf, being recovered by the use of the ecto-5'nucleotidase inhibitor in those animails exposed to ethanol in the pharyngula stage. At 12 mpf there were no significant changes. These results are in agreement with a series of studies that show the importance of adenosinergic signaling during development, as well as the deleterious effects of disturbances in this signaling pathway. The results of this thesis, in contribution to what is in the literature, indicate that the modulation of adenosinergic signaling, especially compensatory adjustments between ecto-5'-nucleotidase and nucleoside transporters, may be important targets of gestational exposure to ethanol.